ANALISIS FAKTOR-FAKTOR MAKROEKONOMI YANG MEMPENGARUHI INDEKS SAHAM LQ45 - Budidarma, I Gusti Agung Musa (JBE (Journal of Business and Economics); Volume 13 No.1, 2014 JBE UNKLAB, 2014)
This  study  aims  to  analyze  the  impact  of  macroeconomic  variables  toward  the  LQ45 stock index.  The macroeconomic variables (independent variables) consist of inflation, money supply, BI rate, and exchange rate  of  IDR/USD, and the dependant variable is LQ45 stock index. This study conducts the simple regression and multiple regression method.  The results of this study show that partially BI rate and exchange rate of IDR/USD affect LQ45 stock index. Furthermore, Inflation rate and money supply partially does not affect LQ45 stock index. However, inflation, money supply, BI rate and exchange rate of IDR/USD simultaneously affect LQ45 stock index.  It implies that investor should consider macroeconomics factors when making investment decision especially for stocks in LQ45 stock index.